2006
DOI: 10.1111/j.1399-6576.2006.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

A porcine model of acute quadriplegic myopathy: a feasibility study

Abstract: The present porcine AQM model demonstrated findings largely in accordance with results previously reported in patients and offers a feasible approach to future mechanistic studies aimed at identifying underlying mechanisms and developing improved diagnostic tests and intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 37 publications
4
60
0
1
Order By: Relevance
“…Previously, experiments with the porcine model were typically for shorter durations, i.e., a day or less. In pilot experiments, it was shown that mechanically ventilated pigs exposed to NMB, systemic administration of corticosteroids, and sepsis for 5 days developed an electrophysiological phenotype resembling previous observations in ICU patients with CIM, i.e., reduced compound muscle action potential (CMAP) amplitudes with maintained motor nerve conduction velocity and intact sensory nerve action potential amplitude and conduction velocity (511,517 ) (FIGURE 14C). This model was subsequently used in a series of studies focusing on the relative importance of different trigger agents such as neuromuscular blockade, sepsis, and steroids in the pathogenesis of CIM, muscle specific differences, as well as the effects of a Ca 2ϩ sensitizer on diaphragm muscle fiber function (1,2,32,511,517,520,566,686).…”
Section: Porcine Icu Modelmentioning
confidence: 72%
See 2 more Smart Citations
“…Previously, experiments with the porcine model were typically for shorter durations, i.e., a day or less. In pilot experiments, it was shown that mechanically ventilated pigs exposed to NMB, systemic administration of corticosteroids, and sepsis for 5 days developed an electrophysiological phenotype resembling previous observations in ICU patients with CIM, i.e., reduced compound muscle action potential (CMAP) amplitudes with maintained motor nerve conduction velocity and intact sensory nerve action potential amplitude and conduction velocity (511,517 ) (FIGURE 14C). This model was subsequently used in a series of studies focusing on the relative importance of different trigger agents such as neuromuscular blockade, sepsis, and steroids in the pathogenesis of CIM, muscle specific differences, as well as the effects of a Ca 2ϩ sensitizer on diaphragm muscle fiber function (1,2,32,511,517,520,566,686).…”
Section: Porcine Icu Modelmentioning
confidence: 72%
“…Furthermore, the complete "mechanical silencing," unique for ICU patients, has been shown to play an important role in the development of CIM in experimental and clinical studies (435,517,574). An additional factor that needs to be taken into account is the relatively long delay between exposure to trigger factors and the phenotype characterizing CIM, i.e., severe muscle wasting and preferential myosin loss (399,511,610). The preferential and significant myosin loss is the result of both a decreased synthesis at the transcriptional level and increased myofibrillar protein degradation (399,434,496,513,517).…”
Section: A the Problem Of Choosing The Right Animal Model: Matching mentioning
confidence: 99%
See 1 more Smart Citation
“…Myostatin inhibits activation of the Akt/mTOR/ p70S6 protein synthesis pathway, which mediates both differentiation in myoblasts and hypertrophy in myotubes (65). In our previous study using the porcine ICU model, where piglets were exposed to only immobilization and mechanical ventilation for 5 days, activin receptor type-2B (ACVR2B) was downregulated more than twofold, and biceps femoris fiber size and force generating capacity were maintained in these animals (6,47). ACVR2B is associated with myostatin binding/signaling, and its strong impact on skeletal muscle has been confirmed in transgenic mice, where a dominant-negative form of ACVR2B has been shown to cause a significant increase in muscle mass (39).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription and quantitative PCR analysis was performed as previously described (47). Briefly, total RNA (100 ng) was reverse transcribed to cDNA using Qscript cDNA supermix (Quanta Biosciences).…”
Section: Methodsmentioning
confidence: 99%